Defect in dissemination of fish breeding and other related technologies raise a question of sustainability to the aquaculture sector of three eastern states of India - Chattopadhyay, N.R. (JOURNAL OF ADVANCES IN BIOTECHNOLOGY, 2012)
Through the implementation of induced breeding technology into farming condition, fish production from inland sector increased substantially from 0.9 million tones in 1977-78 to 1.54 million tones in 1990-91, as the major hatcheries in Bengal has come up in 1980s. Following the Bengal, the fish breeders of Assam and Bihar started establishing hatchery after getting primary training from Bengal breeders. Within very short period of introduction of technology, the greedy and ignorant farmers of the three states started practicing improper breeding practices like mixed spawning, use of small number of breeding population and indiscriminate hybridization for their profit and convenience. Mixed spawning leads to hybridization inadvertently and ultimately affect the native gene pool. Maintenance of small number of founder population leads to inbreeding and the obvious genetic consequences are the increased fry deformities (37.6%), decreased food conversion efficiency (15.6%) and fry survival (19%). Again the undesirable hybrids when find their way into natural system results in genetic intermixing and affects the genetic biodiversity of the native fish fauna. Along with these the fish breeders are introducing alien fishes almost every year without maintaining any code of practice. This alien introduction and repeated use of unauthorized drugs and feeds (composition totally unknown) severely affecting the native biodiversity and unless checked early it may lead to the extinction of some of the prized fishes of India.